Emergency Cerclage in Singleton Pregnancies With Painless Cervical Dilatation: A Meta-analysis. Issue 3 (25th September 2021) - Chatzakis, C.; Efthymiou, A.; Sotiriadis, A.; Makrydimas, G.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:1444–1457) Cervical insufficiency in the second trimester has essentially 3 treatment options at the discretion of the clinician: expectant management, placement of a cervical pessary, and placement of cervical cerclage. These methods are typically used in addition to courses of antibiotics, additional prescriptions (ie, progesterone, corticosteroids), and bed rest. This meta-analysis aimed to compare emergency cerclage versus expectant management for maternal and perinatal outcomes, as well as to identify areas requiring additional or better-quality clinical evidence.